Sociolinguistic Analysis ofTED Talk “We Should All Be Feminists”: A Feministic Perspective (Journal of Asian Development Studies, 2024)
This research paper examines the complex interplay between language, feminism and social expectations through the sociolinguistic analysis of “TED talk ‘We Should All Be Feminists’ by Chimamanda Ngozi Adichie,” taken as a sample. The dialogues used in the talk were transcribed. The study explores the use of the Nigerian English dialect in Adichie’s talk, highlighting its cultural authenticity and the effect of language on propagating feminist ideals. Through descriptive and qualitative methodology, the study challenges conventional gender norms expressed in the speech, shedding light on social variables such as language use, culture, power dynamics and gender inequality. Besides this, the paper focuses on reshaping social expectations and abandoning gender discrimination. It contributes significant insights into gender studiesand linguistics, underscoring the vitality of language in social progress and in shaping feminist discourse. Hence, comprehending the power of language to shape perspectives enables one to foster inclusivity and challenge biases. Therefore, this study is crucial for advocating social change and empowering individuals to reshape and challenge entrenched gender norms. Overall, this research highlights universal issues of social justice and gender stereotypes. It ensures solidarity in the struggle for gender equality globally by examining the intersection of feminism, language and culture.